MAIA, Fc receptor-like 3, supersedes JUNO as IZUMO1 receptor during human fertilization - Vondrakova, Jana; Frolikova, Michaela; Ded, Lukas; Cerny, Jiri; Postlerova, Pavla; Palenikova, Veronika; Simonik, Ondrej; Nahacka, Zuzana; Basus, Krystof; Valášková, Eliška; Machan, Radek; Pacey, Allan; et al. (Science advances, 2022)
Gamete fusion is a critical event of mammalian fertilization. A random one-bead one-compound combinatorial peptide library represented synthetic human egg mimics and identified a previously unidentified ligand as Fc receptor-like 3, named MAIA after the mythological goddess intertwined with JUNO. This immunoglobulin super family receptor was expressed on human oolemma and played a major role during sperm-egg adhesion and fusion. MAIA forms a highly stable interaction with the known IZUMO1/JUNO sperm-egg complex, permitting specific gamete fusion. The complexity of the MAIA isotype may offer a cryptic sexual selection mechanism to avoid genetic incompatibility and achieve favorable fitness outcomes.